The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1590/1807-1929/agriambi.v24n6p415-421
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of broilers subjected to different light spectra and illuminances

Abstract: ABSTRACT The ideal illuminance in poultry houses for broiler chickens may lead to improvement in housing efficiency and broiler welfare. In this context, the objective of this research was to evaluate the behavior and welfare of broiler chickens under effect of illuminance by light-emitting diode (LED) in white band (400-760 nm) and blue/green band (470-525 nm). The experiment was conducted from October to December 2017, in the municipality of Carpina, PE, Brazil, and had 384-oneday-old chicks (mixed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Dustbathing is suggested to be stimulated by sunlight (Duncan et al., 1998 ). Other environmental factors such as inappropriate lighting management (Lucena et al., 2020 ), along with other factors leading to decreased health status (Abeyesinghe et al., 2021 ) of the individual will display the major hazards for this behavioural trait. Ongoing scientific work addresses the optimisation of the light intensity and light colour, or which combination supports the behaviour of the animals (Blatchford et al., 2012 ; Huth and Archer, 2015 ).…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Dustbathing is suggested to be stimulated by sunlight (Duncan et al., 1998 ). Other environmental factors such as inappropriate lighting management (Lucena et al., 2020 ), along with other factors leading to decreased health status (Abeyesinghe et al., 2021 ) of the individual will display the major hazards for this behavioural trait. Ongoing scientific work addresses the optimisation of the light intensity and light colour, or which combination supports the behaviour of the animals (Blatchford et al., 2012 ; Huth and Archer, 2015 ).…”
Section: Assessmentmentioning
confidence: 99%
“…More knowledge might be available for the appropriate light spectrum. Whereas broilers were found to show more comfort behaviours in blue and green light, more discomfort and aggression was found under white light conditions (Lucena et al., 2020 ) and more locomotion under red and yellow light (Sultana et al., 2013 ). The full daylight spectrum composition including UV might contribute to broiler welfare (de Jong and Gunnink, 2019 ) as it has also been shown for laying hens (Wichman et al., 2021 ).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Birds express themselves through their behavior, which is influenced by the characteristics of the breeding environment. Factors related to lighting such as illuminance, wavelength, and lighting programs directly affect the physiological development of the bird (Lucena et al, 2020).…”
Section: Poultry Farming and Lightningmentioning
confidence: 99%
“… Hesham et al (2018) demonstrated that broilers raised under red light displayed higher levels of aggression and feather pecking due to increased activity. Broilers exhibited less fear ( Mohamed et al, 2017 ) and aggressive behavior, were less active ( Khaliq et al, 2018 ) and displayed more comfort and nutritive behaviors when raised under short wavelengths, such as blue and green ( Lucena et al, 2020 ). The authors believed this effect was due to photons of longer wavelength being more effective at penetrating the hypothalamic photoreceptors than those of shorter wavelength, a characteristic that was demonstrated by Hartwigg and van Veen (1979) .…”
Section: Introductionmentioning
confidence: 99%